Experimental study of recovery time of a bulk gallium arsenide avalanche semiconductor switch in low‐energy‐triggered mode. Issue 12 (1st June 2019) - Hu, Long; Wang, Yaogong; Xu, Ming
Abstract : The authors present an experimental study of recovery time of a bulk gallium arsenide (GaAs) avalanche semiconductor switch that operates in low‐energy‐triggered mode. The voltage‐biased bulk GaAs avalanche semiconductor switch is first triggered to be in a conducting state by a laser pulse, and then the other biased voltage is applied without laser triggering after a delay time. The self‐breakdown will be observed experimentally in the bulk GaAs avalanche semiconductor switch by reduction of the delay time, and the recovery time can be achieved accordingly. When the biased voltage of the 0.625 mm thickn switch decreases from 5.0 to 2.0 kV the recovery time reduces from ∼4.4 to ∼1.3 µs.